The Qur'an as the Primary Source of Islamic Teachings: Theological, Epistemological, Legal Foundations, and Contemporary Relevance - Rafif Akhdan Arasyi; Muhamad Jacky Al Malvin; Ikhsan Maulana Fauzi; Muhammad Raditya Rizky Ramadhan; Bina Prima Panggayuh (Konsultan Jurnal Ilmiah Indonesia, 2025)
The Qur’an functions as the primary foundation of Islamic teachings, providing theological guidance, an integrated epistemological framework, legal principles, and ethical directives relevant to contemporary life. This study examines the Qur’an through five major dimensions: its theological role as divine revelation, its epistemological structure integrating textual, rational, and spiritual approaches, its authority as the basis of Islamic law, its ethical contribution to the development of civilization, and its relevance to modern challenges such as science, technology, social change, and moral crises. The findings show that the Qur’an harmonizes faith, intellect, and moral action through universal values such as justice, compassion, responsibility, and human dignity. Legally, the Qur’an offers fundamental principles that can be developed through ijtihād and maqāṣid al-sharī‘ah to address contemporary issues. In education and civilization-building, the Qur’anic worldview encourages holistic human development and balanced social order. This study concludes that the Qur’an remains profoundly relevant for shaping a modern Islamic society that is ethical, intellectual, and justice-oriented, provided it is approached with contextual understanding and sound methodology.